Seeking Refuge: An Exploration of Unaccompanied Women, Minors from Somalia and Families from Pakistan Experiences of Services in Bangkok, Thailand - Aster S. Tecle (Advances in Social Work, 2018)
The number of unprotected urban refugees in Bangkok has grown over the past few years with new migrations of young women, men and families from Somalia and Pakistan. An urban environment can mean opportunity for some but for many the environment can increase vulnerability to exploitation and detention. This study aimed to explore refugees’ experiences in Bangkok, assess agencies’ service delivery models, and strengthen their capabilities to address service gaps. Participants were recruited using purposeful sampling and snowball. Using CBPR, focus groups discussion with Somali and Pakistani refugees (n=63) and individual interviews (n=42) were conducted. Agencies’ staff (n=23) were interviewed regarding challenges in providing services to refugees. Qualitative data analysis revealed four major themes: lack of basic need, problems with legal services, agencies revealed urgent need for shifting from emergency services towards long-term strategies given the protracted immigration status of urban refugees, and the need for a collaborative approach in service provision emerged as an urgent call. Implications to social work practice with urban refugees focusing on potentials for innovative service provision and collective agency responses are discussed.